AB0236 Development and validation of a sensitive lc-ms/ms-based method for analysis of enzymatic activity of folylpolyglutamate synthetase and methotrexate polyglutamates in peripheral blood mononuclear cells of rheumatoid arthritis patients. (12th June 2018) - Muller, I.B.; Heydari, P.; Lin, M.; Struys, E.A.; Hebing, R.; van der Laken, C.J.; van Schaardenburg, D.; Nurmohamed, M.T.; Lems, W.F.; Cloos, J.; Jansen, G.; de Jonge, R.
Abstract : Background: Methotrexate (MTX) is a widely applied anti-rheumatic and anti-leukemic drug. For its intracellular retention and pharmacologic activity, MTX relies on the enzymatic activity of folylpolyglutamate synthetase (FPGS) to convert MTX into its polyglutamate forms (MTX-PG2–6 ). Loss of FPGS activity is associated with reduced MTX activity and although red blood cell (RBC) MTX-PGn levels correlate with disease activity in RA patients, 1 it is anticipated to be more relevant to measure MTX-PGn in peripheral blood mononuclear cells (PBMCs). Thus, the aim of our study was to develop a LC-MS/MS method to 1) measure FPGS activity replacing laborious radioactive assays, and 2) to measure MTX-PGn in PBMCs. 2 Objectives: To validate a rapid, sensitive and non-radioactive assay to measure FPGS activity and MTX-PGn in PBMCs based on LC-MS/MS technology. Methods: Protein extracts (n=5) of PBMCs of MTX-treated RA patients were incubated for 2 hours at 37°C in FPGS assay buffer (pH8.8) containing 250 µM MTX and 4 mM l-glutamic acid as substrates. Next, MTX-PG2 formation was analysed with AB Sciex 4000 Q Trap tandem mass spectrometer coupled to an Acquity Ultra Performance LC system. Measurement of PBMC-MTX-PGn (n=5) was performed by extraction of MTX-PGn from PBMCs by perchloric acid precipitation. Quantification was performed with 13 C5 15 N-labelled MTX-PG1–5 internal standards. In FPGS activity and MTX-PG validation studies, human CCRF-CEM leukaemia cells, CEM/R30dm (a FPGS-deficient, MTX-resistant subline of CCRF-CEM), and human acute lymphoblastic leukemic (ALL) cells served as reference. Results: In CCRF-CEM, the FPGS enzymatic assay showed linearity with protein input (10–250 µg) and incubation time (0.5–3 hours). Substrate affinity parameters (Km) for MTX (65 µM) and l-glutamic acid (2.2 mM) were consistent with earlier reports. 3 FPGS activity in CEM/R30dm was <1% of CCRF-CEM. FPGS activity in ALL blasts was similar to CCRF-CEM while FPGS activity in RA patient PBMCs was 1%–5% of CCRF-CEM, and was non-detectable in RBCs. Average individual fractions of total MTX-PGn in RA patient PBMCs were 22, 1% (range: 8.2%–36.2%) for MTX-PG2, 32.8% (27.1%–43.6%) for MTX-PG3, 34.4% (30.4%–41.3%) for MTX-PG4 and 10.6% (0.0%–28.4%) for MTX-PG5 . Average total MTX-PGn levels per number of RA patient PBMCs were 30–50 fold higher than matched numbers of erythrocytes, and 6–9 fold lower than ALL blasts incubated for 24 hours with 1 µM MTX. Conclusions: A sensitive LC-MS/MS based method was developed for the measurement of FPGS activity and MTX-PGn levels in PBMCs of RA patients. This method holds promise to guide future MTX-therapy response evaluations. References: [1] de Rotte MC, et al. Ann Rheum Dis2015;74:408–414. [2] Jansen G, et al. Oncology Res1992;4:299–305. [3] Liani E, et al. Int. J. Cancer2003;103:587–599. Disclosure of Interest: None declared